2010
DOI: 10.1111/j.1464-0597.2009.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

How is Well‐Being Related to Membership in New Religious Movements? An Application of Person–Environment Fit Theory

Abstract: Ongoing public discussion about the consequences of membership in new religious movements (NRMs) and the lack of studies concerning the relationship between the fit of the person with his or her NRM and well-being together call for a theoretically based investigation of the phenomenon. Hence, this German study on new members of three NRMs applied person-environment fit theory to investigate whether the fit between persons' needs for autonomy and relatedness, on the one hand, and the commensurate supplies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Community integration. To measure integration, we utilized the Religious Community Integration scale (Namini, Appel, Jurgensen, & Murken, 2010). It contains five items, such as "Feeling welcome and integrated in the religious community" and "Being able to successfully integrate one's abilities into the religious community and its practices," which are scored on a 5-point scale ranging from "not at all" (1) to "very much" (5).…”
Section: Methodsmentioning
confidence: 99%
“…Community integration. To measure integration, we utilized the Religious Community Integration scale (Namini, Appel, Jurgensen, & Murken, 2010). It contains five items, such as "Feeling welcome and integrated in the religious community" and "Being able to successfully integrate one's abilities into the religious community and its practices," which are scored on a 5-point scale ranging from "not at all" (1) to "very much" (5).…”
Section: Methodsmentioning
confidence: 99%
“…Another study (Pargament, Johnson, Echemendia, & Silverman, 1985) showed a positive correlation between members' tolerance for ambiguity and satisfaction with aspects of the congregation, for churches that were autonomous and open to 8 CHRISTIAN CONVERSION different views, but a negative correlation for churches that were less open and autonomous. Namini, Appel, Jürgensen, and Murken (2010) showed that the fit between the adherents' psychological need and the religious groups' supply was related to satisfaction with the religious affiliation and low depression.…”
Section: Psychological Antecedents Of Religious Conversionmentioning
confidence: 99%
“…The theory of P-E Fit is consistent with psychological and behavioral studies on new employees (Namini et al, 2010). Moreover, scholars categorized P-E Fit in various manners; for example, Judge and Ferris (1992) and Kristof-Brown (1996) proposed P-O Fit, P-G Fit, P-V Fit, and P-J Fit.…”
Section: Person-environment Fit (P-e Fit)mentioning
confidence: 61%